The Relationship between Physical Activity and FEV1/FVC in Asthmatics - Andis Putri Nawangasri; Budiono Budiono; Arief Bakhtiar; Budi Sutikno; Esti Maulidya Suryaningrum; Dahlia Damayanti (Surabaya Physical Medicine and Rehabilitation Journal, 2022)
Background: Physical activity is any body movement that requires energy expenditure. Minimum physical activities per day can bring good impact for asthmatic patients (e.g.,reduce asthma symptoms). Many asthmatic patients limit their physical activity, so they tend to be inactive.Aim: To analyze the relationship between physical activity level and FEV1/FVC in asthmatics.Material and methods: This was an analytic observational study with a cross-sectional design. The number of participants in this study was 16 respondents (13 females and 3 males) who were recruited based on inclusion and exclusion criteria. The independent variable in this study is levels of physical activity and the dependent variable is FEV1/FVC values. This study study used the International Physical Activity Questionnaire (IPAQ) short form and spirometry test. The data were analyzed with Spearman's rho test.Result: There was a strong association between levels of physical activity with FEV1/FVC values (p=0,012).Conclusions: Increasing level of physical activity in asthmatics can improve their lung function showed by increased FEV1/FVC values.